Seasonal variations in response of periphytic algal community to nutrient enrichment in the river Ganga (Varanasi, India) - Yadav A.; Kumar D.; Singh R.S.; Pandey L.K.; Rai J. (My University, 2025)
Effect of nutrient enrichment on the growth of periphytic algae was studied deploying chemical diffusing substrates in the river Ganga at Varanasi, India. Results depicted seasonal and nutrient induced changes in the species composition of the periphytic algal community. The growth was primarily N-limited and showed secondary P-limitation. © 2018 EDP Sciences.